Ethical Governance In The Transformation Of Digital Public Services At The Population And Civil Registration Office Of Sumedang Regency - Dewi Maharani; Dhesti Widya Nurhasanah Ningrum; Fepi Febianti; Arip Rahman Sudrajat (UNIVERSITAS PAKUAN, 2026)
Digital public service transformation requires not only greater efficiency and service accessibility but also governance that ensures integrity, fairness, transparency, accountability, and the protection of citizens’ data. This study aims to analyze the implementation of ethical governance in digital public service transformation at the Population and Civil Registration Office of Sumedang Regency. The study employed a qualitative approach with a single-case study design. Data were collected through non-participant observation, documentation, and semi-structured interviews with purposively selected informants representing organizational leaders, division heads, service officers, system operators, and citizens using digital services. The study focused on ethical leadership, ethical standards and codes, ethical organizational culture, accountability and controlling, and ethics education and communication. Data were analyzed using an interactive model comprising data reduction, data display, conclusion drawing, and verification, while data validity was maintained through source and technique triangulation. The findings indicate that ethical governance has been supported by leadership role modelling, standard operating procedures and ethical codes, access restrictions, individual user accounts, multi-level verification, a culture of integrity, system activity records, hierarchical controlling, and employee development. However, its implementation has not been fully optimal due to inconsistent complaint follow-up, reactive use of audit trails, irregular security audits, insufficient protection for internal reporters, the absence of specific and periodic digital ethics training, and limited transparency and clarity in communicating data protection and service status. The study concludes that ethical governance has been institutionalized in internal policies and practices, but further strengthening is required to ensure that its outcomes are consistently experienced by citizens through secure, responsive, transparent, inclusive, and public-oriented digital services.